Two Sides of a Barricade (Dis)order and Summit Protest in Europe - Scholl, Christian (SUNY Press Open Access; SUNY series, Praxis: Theory in Action, 2013)
Investigates how activists confront global powers with their street-level dissent.Two Sides of a Barricade argues that to construct global democracy, conflict and dissent must be taken seriously. Christian Scholl explores the political significance of the confrontations within four sites of interaction: bodies, space, communication, and law. Each site of struggle provides a different entry point to understand the influence of protester and police tactics on each other. At the same time, the four sites of struggle allow a comprehensive analysis of how the contestation of global hegemonic forces during summit protests trigger a preemptive shift in social control through increased deployment of biopolitical forms of power.Christian Scholl is Lecturer in Political Science at the University of Amsterdam in the Netherlands. He is the coauthor (with Amory Starr and Luis Fernandez) of Shutting Down the Streets: Political Violence and Social Control in the Global Era.